Mathematical literacy of prospective mathematics teacher based on cognitive style - Santoso, Fransiskus Gatot Iman; Ana Easti Rahayu Maya Sari (Universitas Hamzanwadi, 2025)
Mathematical literacy has become a crucial competency that prospective mathematics teachers must master, especially in the context of globalization. However, a significant challenge is the low mathematical literacy skills, particularly in communication, reasoning, and mathematical modeling. This study aims to analyze the mathematical literacy skills of prospective mathematics teachers based on their cognitive styles, namely field-independent (FI) and field-dependent (FD). A descriptive qualitative approach was used with four students selected based on cognitive style tests and mathematical literacy tests. The instruments used included PISA-based mathematical literacy tests, the Group Embedded Figures Test (GEFT), semi-structured interviews, and observation sheets. The results indicated that students with the FI cognitive style exhibited better communication, mathematization, representation, and reasoning skills, especially in numerical-based problems. In contrast, students with the FD cognitive style faced difficulties in mathematics, representation, and using symbols and diagrams, particularly in data-based and visual problems. Cognitive style plays a significant role in shaping students' mathematical literacy skills and should be considered in teacher education programs.